Penyelesaian Sengketa Sertifikat Ganda Kepemilikan Hak Atas Tanah - Rahayu, Anjani Puji; Junaidi, Arif; Fatmawati, Ina; Lailiyah, Melly Rifa'atul (JURNAL RUANG HUKUM, 2024)
This writing aims to the Concept of Settlement of Land Rights and also to find out how the Settlement Procedure for Proving Land Rights that Occurs Due to Double Certificates. The research method used to study this research problem is normative law research. Normative research is the process of finding legal rules, legal principles, and doctrines to answer legal questions. The term independent and independent variables are still foreign in normative research because normative research does not have to start with a hypothesis. This study is a normative legal research in which researchers conduct analysis to resolve disputes over ownership of double certificated land. The conclusion of this writing is that there are several ways for the Concept of Land Rights Ownership, including: (1) Laws and Regulations on Land Ownership and Registration, (2) Land Registration Reasons, and the (3) Land Rights Status. In this writing, there is also a Procedure for Solving the Proof of Land Rights that Occurs Due to Double Certificates, the process of which is divided into several settlement theories, namely there is a Free Proof Theory and a Bound Proof Theory.